Lack of effect of citalopram on magnetic resonance spectroscopy measures of glutamate and glutamine in frontal cortex of healthy volunteers. - Taylor, M; Norbury, R; Murphy, S; Rudebeck, S; Jezzard, P; Cowen, P (2010)
Magnetic resonance spectroscopy (MRS) is a non-invasive imaging technique that can provide localised measures of brain chemistry in vivo. We previously found that healthy volunteers receiving the selective serotonin reuptake inhibitor, citalopram, daily for 1 week showed higher levels of a combined measure of glutamate and glutamine (Glx) in occipital cortex than those receiving placebo. The aim of this study was to assess if a similar effect could be detected in the frontal brain region. Twenty-three healthy volunteers randomised to receive either citalopram 20 mg or a placebo capsule daily for 7-10 days were studied and scanned using a 3T Varian INOVA system before and at the end of treatment. Standard short-TE (echo time) PRESS (Point-resolved spectroscopy) (TE = 26 ms) and PRESS-J spectra were acquired from a single 8-cm(3) voxel in a frontal region incorporating anterior cingulate cortex. Glutamate and total Glx levels were quantified both relative to creatine and as absolute levels. Relative to placebo, citalopram produced no change in Glx or glutamate alone at the end of the study. Similarly, no effect was seen on other MRS measures studied: myo-inositol, choline, N-acetylaspartate and creatine. These data suggest that the effects of serotonin reuptake to modify cortical glutamatergic MRS measures may be regionally specific. This supports the potential for MRS in assessing neuroanatomically specific serotonin-glutamate interactions in the human brain.